Empowering Senior Adults in the Digital Age: A Bibliometric Analysis of Enhancing ICT Skills in Training Programs at Daoer Zenee Paroki Santo Antonius, Jakarta, Indonesia - Herlina, Maria Grace; Maryani, Maryani; Siswantini, Siswantini (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Purpose – This study explores the impact of Information and Communication Technology (ICT) training programs on empowering senior adults in Jakarta, Indonesia, with a focus on enhancing digital literacy, social inclusion, and overall well-being. Recognizing the global challenge of digital illiteracy among seniors, the research aims to identify effective strategies for fostering ICT skills that promote independence and active societal participation. Methodology – Employing a bibliometric analysis and field study methodology, the study adhered to PRISMA guidelines, reviewing 18 empirical studies to extract relevant insights. Findings – The empirical findings highlight that digital literacy, social connectivity, and self-sufficiency are essential ICT capabilities for seniors. Participatory learning and intergenerational support were identified as particularly effective in improving these skills, leading to increased mental well-being, reduced isolation, and enhanced autonomy. Originality – The study’s originality lies in its regional focus, addressing the unique challenges faced by seniors in Jakarta and providing actionable recommendations for tailored ICT training programs. Implications – Practical implications include guiding policymakers and community organizations to develop inclusive, community-based digital literacy initiatives. These efforts are critical to bridging the digital divide, ensuring active ageing, and fostering social inclusion in an increasingly digital world.